THE EFFECT OF WORK-FAMILY CONFLICT TOWARDS WORK STRESS ALSO WORK DISCIPLINE AND ITS IMPACT OVER ORGANIZATIONAL COMMITMENT TO FEMALE EMPLOYEES AT YPK MANDIRI MENTENG HOSPITAL IN CENTRAL JAKARTA - Purwanti, Dewi; Irfan Noviandy Aulia (Dinasti Publisher, 2020)
This research has purpose to analyze those reaction over work family conflict to organizational commitment with work stress and work discipline as mediating variable. Respondents in this research were all female who works as permanent employees at YPK Mandiri Menteng Hospital as many as 103 employees. The analytical method based on Structural Equation Modeling (SEM) with Partial Least Square (PLS) approach. The findings statement were work stress and work discipline has capable to mediate those partial reaction which occurs on work-family conflict to organizational commitment. Work-family conflict has beneficial and significant reaction over work stress, work stress has negative and significant over organizational commitment, work-family conflict has negative and significant reaction against organizational commitment, work-family conflict has negative and significant impact to work discipline, and work discipline has an positive affects and remarkable against organizational commitment.